Anterior Approach to the Neck: Long-Term Follow-Up. (18th April 2020) - Kochuba, Andrew L; Surek, Christopher C; Ordenana, Carlos; Vargo, James; Scomacao, Isis; Duraes, Eliana; Zins, James E
Abstract: Background: The anterior or submental necklift has been well described. Long-term results have been demonstrated in patients with minimal, mild, and moderate skin excess. It relies on the skin's unique ability to contract once separated from its attachments and further enhances the surgical result with treatment of the intermediate layer- subplatysmal fat, anterior digastric, submandibular gland, and platysma. Treatment of this layer differentiates this operation from liposuction and offers benefits beyond liposuction alone. Objectives: The authors sought to assess the long-term success of the anterior necklift for neck rejuvenation and determine its utility in patients with severe cervicomental angles. Methods: This was a single-surgeon, retrospective review of patients who underwent an isolated anterior necklift with no additional procedures between 1998 and 2017. Pre- and postprocedure photographs were scrambled and examined by independent evaluators grading the change in cervicomental angle based on the Knize scale. The reduction in apparent age was calculated utilizing the validated apparent age assessment scale. Results: Twenty-seven patients were evaluated (42% mild and 58% moderate to severe necks preoperatively). The average follow-up was 24.7 months. There was an average 3.6-year age reduction and 1.0-grade improvement in all patients. In moderate to severe necks, there was a 3.9-year age reduction and 1.4-grade improvement in the cervicomental angle following surgery. Conclusions: This study demonstrates the effectiveness of the operation in improving the cervicomental angle and reducing the overall apparent age of patients, even more so in severe cases. The operation is an option for patients who desire neck improvement but are unwilling to undergo a facelift. Level of Evidence: 4: